1999
DOI: 10.1074/jbc.274.36.25350
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Non-competitive Blockers within the γ-Aminobutyric Acid Type A Chloride Channel Using Chemically Reactive Probes as Chemical Sensors for Cysteine Mutants

Abstract: Selected channel-lining cysteine mutants from the M2 segment of rat ␣1 ␥-aminobutyric acid (GABA) type A receptor subunit, at positions 257, 261, 264, and 272 were co-expressed with ␤1 and ␥2 subunits in Xenopus oocytes. They generated functional receptors displaying conductance and response to both GABA and picrotoxinin similar to the wild type ␣1␤1␥2 receptor. Three chemically reactive affinity probes derived from noncompetitive blockers were synthesized to react with the engineered cysteines: 1) dithiane bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…Based on these studies, it has been suggested that the picrotoxin binding site lies between the 2Ј and 6Ј positions of TMII (29,32). However, more recent work has shown that picrotoxin can also protect a cysteine engineered into the extracellular aspect of TMII (17Ј position) from irreversible modification by chemically reactive picrotoxin-related compounds (33). Although not definitive, these data are consistent with earlier suggestions that picrotoxin and related ligands may interact with multiple sites (7,10,34,35).…”
Section: Discussionsupporting
confidence: 79%
“…Based on these studies, it has been suggested that the picrotoxin binding site lies between the 2Ј and 6Ј positions of TMII (29,32). However, more recent work has shown that picrotoxin can also protect a cysteine engineered into the extracellular aspect of TMII (17Ј position) from irreversible modification by chemically reactive picrotoxin-related compounds (33). Although not definitive, these data are consistent with earlier suggestions that picrotoxin and related ligands may interact with multiple sites (7,10,34,35).…”
Section: Discussionsupporting
confidence: 79%
“…␤ 3 homopentamer mutants A-1ЈC, R0ЈC, and R0ЈS block binding, perhaps because of proximity to A2Ј. Sulfhydryl modification at V1ЈC impedes (19). The involvement of 3Ј, directly or by influencing the neighboring A2Ј, is shown by L3ЈF at ␤ 3 of the ␣ 1 ␤ 3 receptor almost abolishing TBPS and PTX binding (20).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular localization of the NCA site defined here (Fig. 1B) was first indicated by mutagenesis studies (16) as A2Ј (17)(18)(19)(20), T6Ј (21,22), and L9Ј (23,24) in the cytoplasmic half of the transmembrane 2 domain of the channel (Fig. 2).…”
mentioning
confidence: 99%
“…This approach has proven to be broadly applicable to other ligand-gated ion channels to probe successfully agonist-(21), antagonist- (22,23), allosteric modulator- (24), and channel blocker-binding sites (25). It consists in a proximity-accelerated chemical reaction between a thiol-reactive ATP analogue and a single free cysteine mutant engineered in the putative ATPbinding site (Fig.…”
mentioning
confidence: 99%